Customer Satisfaction In Higher Education At UIN Bandung: Systematic Literature Review - Heri Setiawan; Rohanda Rohanda (Glosains: Jurnal Sains Global Indonesia, 2025)
This research aims to explore the factors influencing service satisfaction at UIN Bandung by utilizing a Systematic Literature Review (SLR) methodology. Five key factors analysed in this study include: (1) Strengthening Social and Psychological Support, (2) Improving Campus Facilities, (3) Enhancing Student Participation and Feedback in Decision-Making, (4) Quality of Teaching and Curriculum, and (5) Campus Environment and Academic Culture. The findings from the literature review reveal that student satisfaction is significantly impacted by adequate social and psychological support, alongside campus facilities that enhance the teaching and learning process. Additionally, active involvement of students in decision-making and feedback provision fosters a sense of belonging to the campus, thereby increasing satisfaction levels. Moreover, high-quality teaching, paired with a relevant and innovative curriculum, is essential for delivering a fulfilling academic experience. An inclusive and positive campus environment also plays a significant role in enhancing student satisfaction. This research offers valuable insights for enhancing service quality at UIN Bandung by addressing the factors that have a proven effect on student satisfaction.